DARI IMIGRASI MENUJU INTEGRASI: PERANAN ETNIS JAWA DALAM POLITIK DI SURINAME (1991- 2015) - Acep Rahmat; Nana Supriatna; Moch Eryk Kamsori (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
This bachelor thesis titled “The political role of Javanese Ethnic in Suriname (1991- 2015), the main issues raised in this research is “How was the political role of Javanese ethnic in Suriname 1991- 2015?”. The main problem in this thesis divided into four questions, namely: (1) Why did Javanese Ethnic interested in Suriname’s politics? (2) How was the political development in Suriname in 1991- 2015? (3) How was the contribution of Javanese ethnic in Suriname in 1991-2015? (4) How was the impact of the political role of Javanese ethnic in Suriname in 1991- 2015? (3). That four questions become the basic and the main problem in this research. This research uses the historical method includes the four steps in it, such as heuristic, critic, interpretations and historiography. Meanwhile, the data collection techniques that used in this research is literature studies, by examining the sources that relevant with the problems in this research. The approach in this research using interdisciplinary approaches by using the concept of politics, anthropology and sociology. The politics concepts that used is political party and government. The concept used from anthropology is ethnic, and the concepts from sociology is social mobility and adaptation theory. The main content of this research is the role of Javanese ethnic as newcomers in politics in Suriname. This research explains that the existence of discrimination policy by the Suriname’s special autonomy government against Javanese Ethnic who were reputed as the newcomers that made them joined politics in Suriname by establishing Javanese parties, entering the government and parliament, so that giving the impact for the Javanese ethnic on the modern era, there are many important political figures in Suriname who served as the head of parliament, prime minister and the candidate of Suriname’s president.